Quantitative proteomics and transcriptomics reveals metabolic differences in attracting and non-attracting human-in-mouse glioma stem cell xenografts and stromal cells - Norelle C. Wildburger; Cheryl F. Lichti; Richard D. LeDuc; Mary Schmidt; Roger A. Kroes; Joseph R. Moskal; Carol L. Nilsson (EuPA Open Proteomics, 2015)
Bone marrow-derived human mesenchymal stem cells (BM-hMSCs) show promise as cell-based delivery vehicles for anti-glioma therapeutics, due to innate tropism for gliomas. However, in clinically relevant human-in-mouse glioma stem cell xenograft models, BM-hMSCs tropism is variable. We compared the proteomic profile of cancer and stromal cells in GSCXs that attract BM-hMSCs (“attractors”) with those to do not (“non-attractors”) to identify pathways that may modulate BM-hMSC homing, followed by targeted transcriptomics. The results provide the first link between fatty acid metabolism, glucose metabolism, ROS, and N-glycosylation patterns in attractors. Reciprocal expression of these pathways in the stromal cells suggests microenvironmental cross-talk.